Estudo retrospectivo de 1.647 tumores mamários em cães - Oliveira Filho, Jose Carlos de (2010)
Mammary gland tumors are common in dogs and are the most common type of neoplasms of female dogs. The main purposes of this study were to establish the prevalence of the mammary gland tumors, as well as of its different histologic types (neoplastic and non-neoplastic), diagnosed in the Laboratório de Patologia Veterinária of the Universidade Federal de Santa Maria. There were 1,304 biopsy reports of mammary gland tumors between 1990-2008 and 132 necropsy reports of dogs with mammary tumors between 2000-2008. Data about breed, gender, and age of dogs, tumor localization, morphologic diagnosis, and metastasis occurrence were analyzed. In the biopsy cases, 1,495 tumors were diagnosed, considering the presence of more than one type of tumor in some of the dogs. From those, 1,465 were neoplastic and 30 were non-neoplastic. Within the neoplasms, 390 (26.6%) were benign and 1,075 (73.3%) were malignant. The bening/malignant ratio was 1:2.75. Between the years 2000-2008, 1,125 necropsies of dogs were performed, 132 (11.64%) of which had mammary gland tumors. There were 152 morphologic diagnoses, being 150 of neoplastic and 2 of non-neoplastic lesions. Simple carcinoma was the most prevalent histologic type, both among biopsy and necropsy cases. On necropsy cases, metastases to lymph nodes and distant organs were seen in 39 (29.5%) and 64 (53,3%) cases, respectively.